Survivability of Vibrio cholerae O1 in Cooked Rice, Coffee, and Tea - John Yew Huat Tang; Bariah Ibrahim Izenty; Ahmad Juanda Nur’ Izzati; Siti Rahmah Masran; Chew Chieng Yeo; Arshad Roslan; Che Abdullah Abu Bakar (International Journal of Food Science)
This study aimed to investigate the survival of Vibrio cholerae O1 in 3 types of preparation for cooked rice, Oryza sativa L., (plain rice, rice with coconut milk, and rice with ginger); coffee, Coffea canephora, (plain coffee, coffee with sugar, and coffee with sweetened condensed milk); and tea, Camellia sinensis, (plain tea, tea with sugar, and tea with sweetened condensed milk) held at room temperature (27°C). The survival of V. cholerae O1 was determined by spread plate method on TCBS agar. Initial cultures of 8.00 log CFU/mL were inoculated into each food sample. After 6 h incubation, significant growth was only detected in rice with coconut milk (9.67 log CFU/mL; P<0.05). However, all 3 types of rice preparation showed significant growth of V. cholerae after 24 h (P<0.05). For coffee and tea preparations, V. cholerae survived up to 6 h in tea with condensed milk (4.72 log CFU/mL) but not in similar preparation of coffee. This study showed evidence for the survivability of V. cholerae in rice, coffee, and tea. Thus, holding these food and beverages for an extended period of time at room temperature should be avoided.